The role of teacher performance and locus of control in influencing learning achievement - Sherly, Sherly; Dharma, Edy (Institute of Computer Science (IOCS), 2025)
Student learning achievement is one of the main indicators of success in the world of education. This achievement is not only influenced by internal factors of students, such as intellectual ability and motivation, but also by various external factors, including the quality of teaching provided by teachers and locus of control. This research is necessary to determine the degree to which teacher performance and locus of control are able to create an effective and supportive learning environment that ultimately has an impact on improving student learning achievement. Thirty teachers at Sultan Agung Private Junior High School Pematangsiantar participated in a survey as part of this study's quantitative methodology. Data is gathered by means of questionnaire distribution, recordkeeping, and interviews. SPSS is used to process the data. Quantitative descriptive analysis, which includes correlation and determination coefficients, F-test, t-test, multiple linear regression analysis, and basic linear regression analysis, is used to analyze the data. The study's findings demonstrated a strong positive correlation between locus of control and teacher effectiveness in raising student learning accomplishment. Enhancing student learning achievement is significantly impacted by both strong internal locus of control and effective teacher performance. This research provides important implications for education policies to improve the quality of teaching by paying attention to these two factors.